Supersaturation as a Tool For Skin Penetration Enhancement - Cilurzo, Francesco; Casiraghi, Antonella; Selmin, Francesca; Minghetti, Paola (Current Pharmaceutical Design, 2015)
Supersaturated systems have attracted interest to enhance the skin penetration because of the low cost and reduced risks of irritation with respect to other approaches. The mechanism is simply based on the increased drug driving force for transit out of the dosage form and penetrate the stratum corneum. Supersaturated systems can be obtained by preparation of solvent/non-solvent mixtures; or mixtures containing a skin penetrating solvent or a volatile solvent, and quenching. All methods are described to obtain solutions or semisolid preparations; meanwhile the solvent evaporation and quenching can be used in the transdermal patch production. The adopted formulative strategies can increase the drug concentration in the vehicle 5-fold the solubility and the corresponding increment of the thermodynamic activity determines a significant increase of the drug flux through the skin, according to the Fick’s law. The main limitation of supersaturated systems is related to their thermodynamic instability that, leading to drug crystallization in the vehicle, affects the drug skin penetration. Among the possible strategies to avoid or retard this issue the use of polymeric materials appears the most efficacious. However, the crystallization of a drug during storage and/or application on the skin is driven by so many factors that the stability of supersaturated systems is unpredictable. This paper offers a comprehensive review of the literature with the aim to underline the “pros and cons” of the application of supersaturation in transdermal delivery in the light of the theoretical aspects.
Keywords: solvent evaporation